Recent advances in silica glass optical fiber for dosimetry applications - Zubair, H.T.; Begum, M.; Moradi, F.; Rahman, A.K.M. M.; Mahdiraji, G. A.; Oresegun, A.; Louay, G. T.; Omar, N. Y.M.; Khandaker, Mayeen Uddin *; Adikan, F. R. M.; Noor, N. M.; Almugren, K.S.; et al. (IEEE Society, 2020)
In this paper, we review the highly promising silica glass, fabricated as doped and undoped optical fiber for intended use in radiation dosimetry. The dosimetry techniques reviewed here, underpinned by intrinsic and extrinsic defects in silica glass, focus on Thermoluminescence (TL), Optically Stimulated Luminescence (OSL) and Radioluminescence (RL), with occasional references to the much more established Radiation Induced Attenuation (RIA). The other focus in this review is on the various materials that have been reported earlier as dopants and modifiers used in silica glass optical fiber radiation dosimeters. This article also elaborates on recently reported optical fiber structures, namely, cylindrical fibers, photonic crystal fibers and flat fibers, as well as dimensions and shapes used for optimization of dosimeter performance. The various types of optical fiber radiation dosimeters are subsequently reviewed for various applications ranging from medical dosimetry such as in external beam radiotherapy, brachytherapy and diagnostic imaging, as well as in industrial processing and space dosimetry covering a dynamic dose range from μGy to kGy. Investigated dosimetric characteristics include reproducibility, fading, dose response, reciprocity between luminescence yield to dose-rate and energy dependence. The review is completed by a brief discussion on limitations and future developments in optical fiber radiation dosimetry.